Gut regulatory peptides and intestinal permeability in acute infantile gastroenteritis. Issue 3 (March 1992) - Lawson, G R; Nelson, R; Laker, M F; Ghatei, M A; Bloom, S R; Aynsley-Green, A
Abstract : The plasma concentrations of seven gut regulatory peptides were measured in 11 infants suffering from acute gastroenteritis. Samples were taken at the time of the acute illness, upon reintroduction of feeding, and three months after recovery. These results were compared with controls. In the infants with diarrhoea, a massive increase in the fasting plasma mean (SEM) concentrations of enteroglucagon was found at the time of illness (1292 (312) v 79 (27) pmol/l), with concentrations of pancreatic glucagon, peptide tyrosine tyrosine, and motilin also being increased (17.8 (3.1) v 6.3 (1.1) pmol/l, 114.6 (15.2) v 37.0 (11.0) pmol/l, 217.6 (44.1) v 98.5 (18.3 pmol/l) respectively). The preprandial concentrations of motilin were found to be still increased at recovery (183.9 (35.4) pmol/l), but the concentrations of the other three peptides had returned to normal values. No differences in plasma concentrations of vasoactive intestinal polypeptide, neurotensin, or pancreatic polypeptide were found. An increased intestinal permeability was demonstrated at the time of diarrhoea by the urinary ratio of lactulose to mannitol, suggesting simultaneous gut damage. The effects of regulatory peptides may be relevant to the pathophysiology of gastroenteritis in infants.